Impact of Organizational Socialization on Leader-Member Exchange in the Construction Sector of Pakistan - Muhammad, Asghar (2023)
The present study was aimed to explore the direct and indirect impact of organizational socialization on Leader-Member Exchange (LMX) in the construction sector of Pakistan through a mediating and moderating mechanism. By analyzing previous literature on organizational socialization, it was hypothesized that the positive relationship between organizational socialization and Leader-Member Exchange (LMX) is mediated by Perceived Social Validation. While on the other hand, the Person-Environment Fit was taken as moderator between the Organizational Socialization and Perceived Social Validation. A sample of new comers working in 27 construction companies located in Rawalpindi/Islamabad, Pakistan was used for the current study. Amos 20.0 software was used to evaluate the data using a structural equation modeling technique which is commonly used in explanatory studies. The results revealed that Organizational Socialization of new comers in construction companies of Pakistan is positively affected their Leader-Member Exchange (LMX) with their supervisors. In addition to this, Perceived Social Validation have a direct and positive affect on LMX, it also mediated the positive relationship of organizational socialization and Leader-Member Exchange (LMX). It was found that person environment fit moderated significantly the positive association between Organizational Socialization and Perceived Social Validation. Furthermore, through socialization process they become familiar with their immediate supervisors and leaders through which they build strong positive leader-member relationships at work. At the same time, however, the organization should provide a clear signal to leaders that risks related to providing increased autonomy and decision latitude to new employees are acknowledged in the organization and that support is available from their leaders reduce these risks to new hires. Further research is needed in the field by iii including more mediators, moderators and with a longitudinal design to explore new findings in the construction sector of Pakistan.